Sustained reduction of serum neurofilament light chain over 7 years by alemtuzumab in early relapsing–remitting MS. (April 2022) - Kuhle, Jens; Daizadeh, Nadia; Benkert, Pascal; Maceski, Aleksandra; Barro, Christian; Michalak, Zuzanna; Sormani, Maria Pia; Godin, Jean; Shankara, Srinivas; Samad, Tarek A; Jacobs, Alan; Chung, Luke; et al.
Background: Alemtuzumab efficacy and safety was demonstrated in CARE-MS I and extension studies (CAMMS03409; TOPAZ). Objective: Evaluate serum neurofilament light chain (sNfL) in CARE-MS I patients and highly active disease (HAD) subgroup, over 7 and 2 years for alemtuzumab and subcutaneous interferon beta-1a (SC IFNB-1a), respectively. Methods: Patients received SC IFNB-1a 44 µg 3×/week or alemtuzumab 12 mg/day at baseline and month 12, with further as-needed 3-day courses. sNfL was measured using single-molecule array (Simoa™). HAD definition was ⩾2 relapses in year before randomization and ⩾1 baseline gadolinium-enhancing lesion. Results: Baseline median sNfL levels were similar in alemtuzumab ( n = 354) and SC IFNB-1a–treated ( n = 159) patients (31.7 vs 31.4 pg/mL), but decreased with alemtuzumab versus SC IFNB-1a until year 2 (Y2; 13.2 vs 18.7 pg/mL; p < 0.0001); 12.7 pg/mL for alemtuzumab at Y7. Alemtuzumab-treated patients had sNfL at/below healthy control median at Y2 (72% vs 47%; p < 0.0001); 73% for alemtuzumab at Y7. HAD patients ( n = 102) had higher baseline sNfL (49.4 pg/mL) versus overall population; alemtuzumab HAD patients attained similar levels (Y2, 12.8 pg/mL; Y7, 12.7 pg/mL; 75% were at/below control median at Y7). Conclusion: Alemtuzumab was superior to SC IFNB-1a in reducing sNfL, with levels in alemtuzumab patients remaining stable through Y7. ClinicalTrials.gov identifier: NCT00530348, NCT00930553, NCT02255656